Optimization of the preparation conditions for pitch based anode to enhance the electrochemical properties of LIBs - Han, Yu Jin; Hwang, Jin Ung; Kim, Kyoung Soo; Kim, Ji Hong; Lee, Jong Dae; Im, Ji Sun (Journal of industrial and engineering chemistry (Seoul, Korea), 2019)
[Display omitted] The anode of a lithium ion battery was prepared by the thermal treatment of PFO (pyrolysis fuel oil) utilizing the following three steps: PFO→pitch→coke→anode. The PFO-based pitch with a high softening point exhibited high discharge capacity and Coulombic efficiency because of turbostratic disorder within the disordered structures. A two-step intermediate heating process during the (pitch→coke) reaction induced the remaining relatively light components to participate in condensation/cross-linking reactions during anode formation (coke→anode). The intermediate heating provided a high discharge capacity and a first-cycle Coulombic efficiency based on a well-ordered and suitable micropore structure for lithium storage sites.